Characteristics of neutrophil extracellular traps in patients with periodontitis and gingivitis - Fei ZHANG; Xi-Mei YANG; Shu-Yu JIA (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract We sought to compare the characteristics and clinical significance of neutrophil extracellular traps in gingival samples from patients with periodontitis and those with gingivitis. The clinical indexes of gingival samples from patients with periodontitis and gingivitis were measured; the expression of TNF-alpha and IL-8 was measured by real-time fluorescent quantitative PCR; and the expression of TLR-8 and MMP-9 was measured by western blotting assays. Chemotaxis, phagocytosis and phagocytic activity of neutrophils were measured. Compared with the healthy group, the expression of TNF-α and IL-8 in the periodontitis group and the gingivitis group increased significantly (p < 0.05), and TNF-α in the gingivitis group was significantly lower than that in the healthy group (p < 0.05). The expression of IL-8 in the periodontitis group was significantly higher than that in the periodontitis group (p < 0.05). Furthermore, the expression of TLR-8 and MMP-9 in the periodontitis group was different from that in the gingivitis group and the healthy group, and the expression of TLR-8 and MMP-9 in the gingivitis group was significantly different from that in the healthy group (p < 0.05). In addition, the neutrophil mobility index in healthy people was 3.02 ± 0.53, that in the periodontitis group was 2.21 ± 0.13, and that in the gingivitis group was 2.31 ± 0.12. In conclusion, the chemotaxis of neutrophils in gingival samples of patients with periodontitis and gingivitis was decreased, the phagocytotic ability and activity of neutrophils were reduced, and the release of the extracellular trap-releasing inducible factors TNF-alpha and IL-8 also declined.